Facilitating Bedroom Recording Practices - Christopher William Bulgren; Jason C. Fick (Journal of the Association for Technology in Music Instruction, 2025)
An increase in access to recording technology has expanded opportunities for teachers and students. One approach, bedroom recording, involves the use of low-budget hardware and software in common, untreated spaces, often in one’s home. Bedroom recording practices significantly impact the sense of place and workflow in the industry for both professionals and amateur music makers. As an art form that thrives on mobility, bedroom recording is a natural pathway for music students to achieve low-cost, self-guided recordings. The purpose of this study was to explore best practices and student interactions related to a bedroom recording project. Participants were 17 Music Education Majors and 10 Music Technology and Production Majors. Participants from both majors collaborated to record an original song. Exploratory case study methodology was used to gather perceptions of the recording project. Data collection included students completing writing prompts before and after the project. Coding revealed four primary themes: resourcefulness, workflow, communication, and relevant social groups. Findings reveal best practices for bedroom recording include clearly defining roles, facilitating communication, and providing appropriate guidance.
Keywords: technology; recording; education; songwriting; self-mediated learning